Isotropy group on some topological transformation group structures - D. Keerthana; V. Visalakshi (Математичні Студії, 2024)
This paper explores the topological properties of irresolute topological groups, their quotient maps, and the role of topology in normal subgroups. It provides a detailed analysis\linebreak using examples and counterexamples. The study focuses on the essential features of irresolute topological groups and their quotient groups, for understanding the topological aspects of isotropy groups. For a trans\-for\-ma\-tion group $(\mathsf{H}, \mathsf{Y}, ψ)$ and a point $y \in \mathsf{Y},$ the set